Designing Tracking Devices And Controls On Motor Vehicles Using GPS Integrated Internet Of Things - M Dandy Aprillah; Nasron Nasron; Martinus Mujur Rose (Program Studi Teknik Elektro Universitas Khairun, 2021)
Motorcycles are one of the objects that are very prone to be stolen, anticipation of theft is not enough just to install a safety lock, but it needs to be equipped with monitoring and controlling systems to reduce theft of motorcycles because motorcycles aregenerally not equipped with GPS (Global Positioning System). In this final task, a Tracking Device or tracking tool is designed that can work in IoT. IoT (Internet of Things) is a computational concept of everyday objects connected to the internet and able to identify themselves to other devices. NodeMCU ESP8266 and Android smartphone are used as tracking device controller components. The signal or data obtained in the form of vehicle position coordinate data can be seen in googlemaps, and this tool is equipped with a relay that serves as a switch to turn the stolen motor on or off remotely. The test result of this tool, the user can control the motor from a very long distance as long as the deviceand the user still get internet access, the user can only give one command every 15 seconds, be it a command asking for the coordinates of the position of the vehicle or a command to turn off the motor